2017
DOI: 10.1007/s11356-017-9751-5
|View full text |Cite
|
Sign up to set email alerts
|

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress

Abstract: The complex bio-geochemistry of soil allows pollutant to persist for a longer period of time which further decreased the fertility and natural composition of land. Nickel, an inorganic pollutant, coming from a wide range of industrial and manufacturing units possesses serious threat to soil degradation and crop productivity around the world. The present study was carried to evaluate the combined role of microwave irradiation (MR) and citric acid (CA) on the phytoextraction potential of Brassica napus L. under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Plants produce and accumulate osmolytes such as soluble sugars, trehalose, amino acids, and betaines to counteract stress-induced osmotic imbalance. In addition, these osmolytes participate in cellular energy transfer, stabilize membranes and proteins, scavenge ROS, chelate HMs, and minimize metal uptake to cope with metal-induced osmotic, ionic, and oxidative stresses [ 62 , 63 ]. Plants with better osmoprotectant biosynthesis are adaptable to stress [ 64 ].…”
Section: Mechanism Of Heavy-metal-induced Growth Inhibitionmentioning
confidence: 99%
“…Plants produce and accumulate osmolytes such as soluble sugars, trehalose, amino acids, and betaines to counteract stress-induced osmotic imbalance. In addition, these osmolytes participate in cellular energy transfer, stabilize membranes and proteins, scavenge ROS, chelate HMs, and minimize metal uptake to cope with metal-induced osmotic, ionic, and oxidative stresses [ 62 , 63 ]. Plants with better osmoprotectant biosynthesis are adaptable to stress [ 64 ].…”
Section: Mechanism Of Heavy-metal-induced Growth Inhibitionmentioning
confidence: 99%
“…The toxicity of Ni mainly depends on its concentration in media (Rathika et al 2020). Nickel is mostly present in plant roots at high concentrations and less is translocated to aerial parts (Amjad et al 2020;Farid et al 2017). The growth of plant roots was highly altered by Ni as compared to shoots (Antić-Mladenović et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, about 310 plant species have been identified as Ni hyper-accumulators as these plant species can accumulate higher levels of Ni without showing any toxic effects (Genchi et al 2020;Bhalerao et al 2015). In plant cytoplasm, usually high level of Ni was avoided by organic acids as described by Farid et al (2017) and Helaoui et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many HMs (e.g., Pb, copper, cobalt, nickel and cadmium) can affect plant agronomic parameters in a very toxic way [17,18]. Similarly, many researchers have reported that there is a great reduction in biomass of plants, as well as the growth of plants due to metal stress in wheat, rice and Brassica napus L. [19][20][21]. In the present study, the reduction in plant agronomic characteristics with increasing concentrations of Pb was in accordance with the work done by previous researchers [20,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were taken at appropriate wavelengths. The chlorophyll a, chlorophyll b and carotenoids wavelengths used were 644 nm, 663 nm and 452 nm with spectrophotometer (Halo DB-20/DB-20S, Dynamica Company, London, UK) and final measurements were calculated by using the following formulas [17][18][19][20][21][22].…”
Section: Chlorophyll Contents and Gas Exchange Parametersmentioning
confidence: 99%